Effectivity of alkaline water on the clinical improvement in laryngopharyngeal reflux - Muhammad Rizka Yahya; Rery Budiarti; Dwi Antono; . Farokah; . Muyassaroh (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Laryngopharyngeal reflux (LPR) is the reflux of gastric acid through theupper oesophageal sphincter causing mucosal damage of the larynx, thegastrointestinal tract, and the upper airway. Alkaline water has the ability towithstand acidic conditions in the body, the formation of carbonic anhydrase,and reepithelization. This study aimed to investigate the effect of alkaline wateron the clinical improvement in LPR patients. A randomized control trial withpre-test and post-test control group design on LPR patients aged 18 to 60 y.o.was conducted at the ENT-HS outpatient clinic of Dr Kariadi Central Hospital,Semarang, Central Java, Indonesia. Thirty subjects were recruited and dividedinto two group with 15 subjects in each group. In the control group, the subjectswere given standard therapy and mineral water. In the treatment group, thesubjects were given standard therapy and alkaline water. The diagnosis ofLPR was made if the reflux scoring index (RSI) was ≥13, and the reflux findingscore (RFS) was >7. ,After two weeks of intervention, the clinical improvementswere evaluated by reassessing the RSI score. The data were analyzed usingthe Shapiro-Wilk test and independent t-test. The results showed that the mostcommon main complaint was throat clearing [11 subjects (37%)]. Based on theRSI score, there were clinical improvements in both the control (p <0.001) andthe treatment groups (p <0.001). However, there was no significant differencein the RSI score before and after the intervention in the control (p = 0.058)and the treatment groups (p = 0.322). In conclusion,tbe d there is an effect ofalkaline water on the clinical improvement of LPR patients. However, there isno significant difference in the clinical improvement between the control andthe treatment groups.